DuPont System Analysis in Measuring Financial Performance at PT Unilever Tbk During 2019–2023 - Anna Valensia Christianty de Fretes (International Journal Business, Management and Innovation Review, 2025)
This research aims to analyze the financial performance of PT Unilever Tbk during 2019–2023 using the DuPont System method. The DuPont analysis decomposes Return on Equity (ROE) into three components: Net Profit Margin (NPM), Total Asset Turnover (TATO), and Equity Multiplier (EM). The study applies a descriptive quantitative approach with secondary data obtained from the company’s annual financial statements. Results show a consistent decline in all DuPont components, leading to a decrease in ROE throughout the period. The deterioration was driven by internal inefficiencies in asset utilization and cost management, as well as external pressures such as changing consumer behavior, rising competition from local FMCG producers, and geopolitical sentiment toward multinational brands. The findings indicate that PT Unilever’s financial performance falls below the industry standard, highlighting the need for improved operational efficiency, optimal capital structure, and strategic management adjustments to sustain competitiveness.